(3TQM GdedNU aj GdgjFI ddLYejfjs - (3bGVj RGOg, ehSi Hf eMehO Hf GdbGVj, fMh (B840(3g`s ((3eMeO MSjfs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdTeS VjGAhHYO adG CbSe HehGbY GdfLhe hEfg dbSe dh JYdehf YXje Efg aj ReGffG gPGhdbO UfaJ ajgG cJH JdbJ GdNJUQ GdeSei HGdedNU aj GdgjFI MJi JUOi dTQMgs
(3BNQgG (B:s
(3hEMOi hYTQhf SGYI EdG ObjbI hKdK, CNeGS ObjbI ef ObGFb GdSGYGJ Ydi eG PgH Edjg GdSjO deG dG jNai Ydi ef dg OQGjI aj GdMSGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 328s
(3eYLe GdeDdajf(B: 3 / 937s
(3cTa GdXfhf(B: 2 / 1819s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3gjFIs